Operational Modal Analysis of Overpass Malonji (Proceedings of Faculty of Civil Engineering, 2019)
This paper presents the results of an on-site dynamic testing of the pedestrian overpass Malonji using operational modal analysis for obtaining structural modal parameters. The measured modal parameters were compared to the modal parameters calculated on the numerical model of the overpass. It is shown that this type of dynamic testing and data processing can provide a very good match between measured and calculated frequencies. A more accurate determination of modal shapes derived from measured acceleration requires: (i) improvement in the ModalVIEW geometry model, (ii) using a greater number or different positions of accelerometers, (iii) accelerometers with better measuring accuracy.
Keywords: pedestrian overpass; dynamic testing; OMA; ModalVIEW